Integrated Health and Safety Program: PAD Screening for Adults and Disaster Training for Youth in Wombo Kalonggo - irsanty Collein; Baiq Emy Nurmalisa; Andi Fatmawati Syamsu; Fitria Masulilli; Alfrida Semuel Ra'bung; Fajrillah Kolomboy; Helena Pangaribuan; Ismunandar Ismunandar; Supirno Supirno; Eko Kristanto (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2026)
Rural communities in Indonesia face a dual burden of high disaster risk and a growing prevalence of non-communicable diseases (NCDs). A holistic approach addressing both challenges simultaneously may build comprehensive community resilience. This community service initiative aimed to implement and evaluate an integrated program combining disaster response training for youth with Peripheral Artery Disease (PAD) screening in Wombo Kalonggo Village. The program was conducted in February 2025. A two-pronged intervention was delivered: (1) Disaster response training for 50 youth members (Karang Taruna), comprising lectures, hands-on simulations, and a night drill, with pre- and post-training knowledge assessments; and (2) Targeted screening for PAD using the Ankle-Brachial Index (ABI) conducted on 38 high-risk adults aged ≥45 years with at least one risk factor (smoking, diabetes, or hypertension). No follow-up measurement was conducted due to the short-term nature of the program. Results: Disaster training outcomes: Youth disaster knowledge increased from 58% pre-test to 86% post-test. The program initiated a youth disaster preparedness team (not yet formally recognized as a functional organization), Screening outcomes: Among 38 adults screened, mean ABI was 0.945 (SD ±0.066; 95% CI: 0.90–0.98). Integration efficiency: The single-platform model reached both youth and at-risk adults in two village gatherings, though causal synergy between components was not evaluated. Conclusion: This preliminary study demonstrates that integrating disaster preparedness training with NCD screening is logistically feasible in a single-village, short-term community service format. However, claims of effectiveness and replicability are limited by the absence of a control group, lack of long-term follow-up, and short evaluation timeframe. Sustaining youth team activities and incorporating ABI screening into primary healthcare (Puskesmas) require further evaluation. This approach may serve as a preliminary reference for similar vulnerable communities, pending longitudinal validation.